Analysis of the potential impact of genomic variants in global SARS-CoV-2 genomes on molecular diagnostic assays. (January 2021) - Jain, Abhinav; Rophina, Mercy; Mahajan, Saurabh; Krishnan, Bhavya Balaji; Sharma, Manasa; Mandal, Sreya; Fernandez, Teresa; Sultanji, Sumayra; Jolly, Bani; Mathew, Samatha; Sivasubbu, Sridhar; Scaria, Vinod
Graphical abstract: Hightlights Abstract: An epidemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing coronavirus diseases (C0VID-19) initially reported in Wuhan, China has rapidly emerged into a global pandemic affecting millions of people worldwide. Molecular detection of SARS-CoV-2 using reverse transcription polymerase chain reaction (RT-PCR) forms the mainstay in screening, diagnosis and epidemiology of the disease. Since the virus evolves by accumulating base substitutions, mutations in the viral genome could possibly affect the accuracy of RT-PCR-based detection assays. The recent availability of genomes of SARS-CoV-2 isolates motivated us to assess the presence and potential impact of variations in target sites of the oligonucleotide primers and probes used in molecular diagnosis. We catalogued a total of 132 primer or probe sequences from literature and data available in the public domain. Our analysis revealed that a total of 5862 unique genetic variants mapped to at least one of the 132 primer or probe binding sites in the genome. A total of 29 unique variants were present in ≥ 1% of genomes from at least one of the continents (Asia, Africa, Australia, Europe, North America, and South America) that mapped to 36 unique primers or probes binding sites. Similarly, a total of 27 primer or probe binding sites had cumulative variants frequency of ≥ 1% in the global SARS-CoV-2 genomes. These included primers or probes sites which are used worldwide for molecular diagnosis as well as approved by national and international agencies. We also found 286 SARS-CoV-2 genomic regions with low variability at a continuous stretch of ≥ 20bps that could be potentially used for primer designing. This highlights the need for sequencing genomes of emerging pathogens to enable evidence-based policies for development and approval of diagnostics.